An ethnoracial perspective: response to Valdez and Golash-Boza. Issue 13 (21st October 2017) - Aranda, Elizabeth
ABSTRACT: Valdez and Golash-Boza argue that scholarship on race and scholarship on ethnicity have been divorced from each other and call for researchers to put these two paradigms in conversation with one another. I address some of their assertions using previous work, including my own, that has merged racial and ethnic literatures and that has shed new light on old theories, as well as opened the path toward new theories and methods. I argue that an ethnoracial perspective can be leveraged to better understand global racial and ethnic inequalities.